Complex Variant t(9;22) Chromosome Translocations in Five Cases of Chronic Myeloid Leukemia - Ana Valencia; José Cervera; Esperanza Such; Eva Barragán; Pascual Bolufer; Oscar Fuster; Rosa Collado; Jesús Martínez; Miguel A. Sanz (Advances in Hematology)
The Philadelphia (Ph1) chromosome arising from the reciprocal t(9;22) translocation is found in more than 90% of chronic myeloid leukemia (CML) patients and results in the formation of the chimeric fusion gene BCR-ABL. However, a small proportion of patients with CML have simple or complex variants of this translocation, involving various breakpoints in addition to 9q34 and 22q11. We report five CML cases carrying variant Ph translocations involving both chromosomes 9 and 22 as well as chromosomes 3, 5, 7, 8, or 10. G-banding showed a reciprocal three-way translocation involving 3q21, 5q31, 7q32, 8q24, and 10q22 bands. BCR-ABL fusion signal on der(22) was found in all of the cases by FISH.